2016
DOI: 10.7150/jca.16110
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diabetes on the Risk of Prostate Cancer Development according to Body Mass Index: A 10-year Nationwide Cohort Study

Abstract: Purpose: We examined the association between obesity and prostate cancer both with and without diabetic patients included in the analysis using nationally representative data of the Korean population from the National Health Insurance System (NHIS).Materials and Methods: Of the 424,712 participants who underwent health examinations in 2002-2008, 139,519 men ≥40 years old and without prostate cancer were followed from the beginning of 2002 to the end of 2012. Multivariate adjusted Cox regression analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…It is reported that patients underweight or with normal weight may suffer from less beta-cell dysfunction and insulin resistance than those obese [ 14 ], while diabetic patients with higher BMI were more likely to experience insulin resistance due to adiposity [ 15 ]. T2DM and obesity were also observed to jointly promote the development of certain subtypes of cancer, but the results varied by cancer sites and across populations [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that patients underweight or with normal weight may suffer from less beta-cell dysfunction and insulin resistance than those obese [ 14 ], while diabetic patients with higher BMI were more likely to experience insulin resistance due to adiposity [ 15 ]. T2DM and obesity were also observed to jointly promote the development of certain subtypes of cancer, but the results varied by cancer sites and across populations [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer was coded C67. Because the Korean government enhanced benefit coverage for four major conditions (cardiovascular disease, cerebrovascular disease, cancer and rare diseases), all physician-diagnosed cancer patients are registered in the database 17 . Patient identification numbers were anonymized to protect individual privacy.…”
Section: Methodsmentioning
confidence: 99%
“…The cutoff value of WC for abdominal obesity of men was ≥90 cm [9]. Body mass index (BMI) categories, such as underweight (under 18.5), normal weight (18.5-22.9), overweight (23-24.9), and obese (over 25), were from the Korean Society for the Study of Obesity [10]. Finally, the definition of patients with metabolic diseases as used in this manuscript refers to individuals with at least one of the common components of metabolic syndrome (diabetes, hypertension, dyslipidemia).…”
Section: Methodsmentioning
confidence: 99%